1999
DOI: 10.1128/iai.67.11.6034-6039.1999
|View full text |Cite
|
Sign up to set email alerts
|

Laccase ProtectsCryptococcus neoformansfrom Antifungal Activity of Alveolar Macrophages

Abstract: While laccase of Cryptococcus neoformans is implicated in the virulence of the organism, our recent studies showing absence of melanin in the infected mouse brain has led us to a search for alternative roles for laccase in cryptococcosis. We investigated the role of laccase in protection of C. neoformans against murine alveolar macrophage (AM)-mediated antifungal activity by using a pair of congenic laccase-positive (2E-TUC) and laccase-deficient (2E-TU) strains. The laccase-positive cells with laccase derepre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(78 citation statements)
references
References 45 publications
2
75
0
1
Order By: Relevance
“…Laccase activity in C. neoformans is induced by Fe (Zhu and Williamson 2004). It is believed that cryptococcal laccase-iron oxidase activity may protect the fungus from macrophage infections by maintaining Fe in an oxidized form, thereby decreasing the production of antifungal hydroxyl radicals via Fenton reactions (Liu et al 1999). Most recently, the genome of Phanerochaete chrysosporium was searched for laccase-encoding sequences.…”
Section: Sample Culture Conditionsmentioning
confidence: 99%
“…Laccase activity in C. neoformans is induced by Fe (Zhu and Williamson 2004). It is believed that cryptococcal laccase-iron oxidase activity may protect the fungus from macrophage infections by maintaining Fe in an oxidized form, thereby decreasing the production of antifungal hydroxyl radicals via Fenton reactions (Liu et al 1999). Most recently, the genome of Phanerochaete chrysosporium was searched for laccase-encoding sequences.…”
Section: Sample Culture Conditionsmentioning
confidence: 99%
“…For example, the presence of laccase has been shown to result in protection against murine alveolar macrophages without the addition of catecholamines, suggesting an intrinsic protective effect of laccase. In these studies, the finding of a novel iron oxidase activity of cryptococcal laccase as well as abolition of the laccase-protective effect by mannitol and accentuation by iron suggested that laccase may modulate macrophage-dependent Fenton reactions [39]. Another interesting laccase activity is the ability to produce oxygenated lipids from fatty acids [40].…”
Section: Roles Of Laccase-derived Products In the Virulence Of C Neomentioning
confidence: 99%
“…In the environment, induction of fungal laccases by iron has been proposed to modulate iron-catalyzed Fenton reactions during cellulose depolymerization [44]. In the mammalian host, iron within the phagolysosome may induce iron oxidase activity of laccase, which, in turn, reduces potentially toxic Fenton reactants [39]. Other regulatory stimuli are more difficult to understand in relationship to pathogenesis but provide key insights into the regulation of cryptococcal virulence.…”
Section: Molecular Regulation Of Laccase and Signal Transduction Pathmentioning
confidence: 99%
“…One proposed mechanism of laccase-dependent virulence is that the enzyme oxidizes trace amounts of the neurotransmitter dopamine at the pathogen surface which then polymerizes to form melanin-like pigments (Nosanchuk et al ., 1998). Laccase may also have a direct immunoprotective function in the absence of dopamine by scavenging hydroxyl radicals produced by host macrophages by virtue of its Fe(II) oxidase activity (Liu et al ., 1999). Regardless of the mechanism of pathogenesis, expression of the laccase gene in vitro is strictly controlled by various growth conditions.…”
Section: Introductionmentioning
confidence: 99%